Presbyterians in North Carolina Race, Politics, and Religious Identity in Historical Perspective. - Conser, Walter H.; Cain, Robert J. (Knoxville : University of Tennessee Press, 2011)
This volume is the first comprehensive overview of North Carolina Presbyterians to appear in more than a hundred years. Drawing on congregational and administrative histories, personal memoirs, and recent scholarship—while paying close attention to the relevant social, political, and religious contexts of the state and region—Walter Conser and Robert Cain go beyond older approaches to denominational history by focusing on the identity and meaning of the Presbyterian experience in the Old North State from the seventeenth through the twentieth centuries. Conser and Cain ex.
Preface; Part One: Beginnings; 1. Old World Origins and New World Horizons; 2. Atlantic World Bonds and Backcountry Settlers; 3. Revivalism, Reform, and Rancor in the Antebellum Piedmont; 4. Limited and Late; Part Two: Conflict, Renewal, and Reunion; 5. Both Read the Same Bible and Prayed to the Same God; 6. Out from the Gloomy Past; 7. Rebuilding in the Era of the New South; 8. A New Church in a New Era; Suggested Readings; Index
Description based upon print version of record.
Keywords: Presbyterian Church -- North Carolina -- Clergy; Presbyterian Church -- North Carolina -- History; Presbyterian Church; Religion; Presbyterian Church -- North Carolina -- History; RELIGION / Christianity / Presbyterian; Electronic books